PENINGKATAN PROFITABILITAS UKM: SEBUAH PERSPEKTIF ANALISIS EKOSISTEM BISNIS - Sya'roni, Deden Abdul Wahab; Anggadini, Sri Dewi; Yunanto, Rio; Soegoto, Dedi Sulistiyo; Fahrana, Egi; Rosyad, Achmad (Jurnal Riset Akuntansi, 2024)
This study aims to determine the influence of the business ecosystem on the improvement of profitability of Small and Medium Enterprises (SMEs) as a form of business success. The method used is descriptive and verificative with several approaches. The unit of analysis in this study is small businesses, with the unit of observation being business owners. Data processing method utilizes Structural Equation Modeling (SEM), and the data used is primary data. The results indicate the presence of a business ecosystem's influence on the increase in profitability, which impacts business success. The research findings demonstrate that a good business ecosystem can affect the enhancement of profitability. This study is expected to be valid for business practitioners and stakeholders in making decisions to achieve long-term business success.